Relationship between Knowledge Level about Anemia, Parents' Income and Menstrual Pattern with Anemia Status in Young Girls at 7th-Grade Junior High School Students in Palangka Raya City - Theresia, Nita; Putri, Fina Ratih Wira (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Background: One of the most common problems in adolescents was iron anemia. In adolescents who experience anemia, it would had very significant effects such as reduced body fitness, decreased learned abilities, suboptimal height, decreased physical abilities and pale faces. Objective: : To analyze the relationship between knowledge levelled, parental income and menstrual patterns with anemia status in young girls at 7th-grade junior high school in Palangka Raya city. Method: The design of this studied was an analytical descriptive with a quantitative cross-sectional studied, a sample of 146 of 1409 population of 7th-grade students spread across 47 schools in the city of Palangka Raya. The instrument used a knowledge questionnaire and a digital hemometer. The analysis used in this studied was the spearman correlation test and multiple logistic regression. Result: : There was a relationship between the leveled of knowledge of anemia and anemia status in young girls at 7th-grade junior high school in Palangka Raya city (p-value=0.0001;r=0.325). There was a relationship between parents' income and anemia status in young girls at 7th-grade junior high school in Palangka Raya city (p-value=0.0001;r=0.392). There was a relationship between menstrual patterns and anemia status in 7th-grade junior high school girls in Palangka Raya city (p-value=0.006;r=0.227). Parents' income factor was the factor that most influences the incidence of anemia in young women (exp. B=8.241). Conclusion: Knowledge was a protective factor which means a protective action in the form of anemia prevention behaviour. Keywords: Anemia Status, Anemia Knowledge; Menstrual Patterns; Parents Income